The agency of CoCo: Why do banks issue contingent convertible bonds? - Roman Goncharenko; Steven Ongena; Asad Rauf (Goethe University Frankfurt, Center for Financial Studies (CFS), 2017)
Why do banks issue contingent convertible debt? To answer this question we study comprehensive data covering all issues by publicly traded banks in Europe of contingent convertible bonds (CoCos) that count as additional tier 1 capital (AT1). We find that banks with lower asset volatility are more likely to issue AT1 CoCos than their riskier counterparts, but that CDS spreads do not react following issue announcements. Our estimates therefore suggest that agency costs play a crucial role in banks' ability to successfully issue CoCos. The agency costs may be higher for CoCos than for equity explaining why we observe riskier or lowly capitalized banks to issue equity rather than CoCos.
urn:nbn:de:hebis:30:3-437353
Keywords: G01; G12; G24; 330; CoCos; Contingent Convertible Bonds; Bank Capital Structure